Final answer:
To find a2 and a3, we can use the given recursive formula aₙ = 6aₙ₋₁. First, we find a₂ by substituting the value of n as 2, which is equal to -30. Next, we find a₃ by substituting the value of n as 3, which is equal to -180.
Step-by-step explanation:
To find a2 and a3, we can use the given recursive formula an = 6an-1.
First, we find a2 by substituting the value of n as 2 in the formula:
a2 = 6a2-1 = 6a1 = 6(-5) = -30
Next, we find a3 by substituting the value of n as 3 in the formula:
a3 = 6a3-1 = 6a2 = 6(-30) = -180